The symbiotic interaction of Bradyrhizobium japonicum with bambara groundnut and cowpea and the effects of NOD gene-inducers, daidzein and genistein - Salie, S (Department of Biological Sciences, 2017)
The aim of this project was to investigate whether nodulation, and nitrogen concentration of legumes can be increased by providing additional nod geneinducer compounds. Both daidzein and genistein are nod gene-inducers for rhizobia nodulating cowpea, bambara groundnut, soybean and the common bean.